Modlitwa poranna Jezusa (Mk 1,35) - Lesław Daniel Chrupcała (Wrocławski Przegląd Teologiczny)
The study of Mk 1,35 which is situated at the end of the first missionary day of Jesus in Capharnaum (Mk 1,21-34.35-39), is divided into four parts. The first part offers a general presentation of the theme of prayer in the Gospel of Mark, noting the similarities and differences with the other Synoptic Gospels. The second, dedicated to the time and place of daily prayer in the time of Jesus, serves to prepare the ground for the discussion on the prayer of Jesus. Among other things, it can be observed that in the 1st century the Jews certainly practiced personal prayer at different hours of the day (above all the morning and the evening) which was widely diffused, but through the works of the rabbis, this phenomenon would become a religious obligation. Outside the community of Qumran, in the Palestinian environment, there is a lack of relative testimony to night prayer. In the third part, a literary analysis of Mk 1,35 includes the examination of the syntactic structure of the text (1) and philological observations (2). Finally the fourth part proposes a theological commentary of Mk 1,35. Following the internal structure of the passage, it addresses three specific topics: (1) the biblical background of the night prayer of Jesus, (2) a solitary place of prayer, (3) the motive and content of the prayer of Jesus. The principle results of this study are as follows: Taking into consideration the numerous texts of the Old Testament regarding the time of prayer, it is very probably that Jesus would have found inspiration for His night prayer from biblical examples, the Psalms in particular. The act of praying by Jesus therefore reflects the life of a wise man who is guided by the wisdom of God and respects his Law. According to Mark, the night prayer of Jesus emphasized in Mk 1,35 is the example of the Son of God that must be a model for his followers to imitate. The „deserted place” in which Jesus went to pray cannot be identified with the desert. However in the Christological vision of Mark, these two places of wilderness are linked. In fact Mk 1,35 should be seen in relation to two other texts that speak also of a retreat into a „deserted place” (1,45; 6,31-33). This connection makes one think that Jesus had purposely chosen a deserted place because it recalled the place where he defeated Satan and where he overcame temptation before beginning his public mission (Mk 1,12-13). This Christological interpretation of the deserted place helps one to understand better the motive and the content of the night prayer of Jesus. The Gospel of Mark presents three episodes in which the prayer of Jesus occurs (Mk 1,35-39; 6,42-52; 14,2642), situated in a similar scenario and at a critical moment in His life. In the light of its context, it does not seem that the prayer of Jesus in Mk 1,35 had considered the universal dimension of His mission (Mk 1,38) which was well noted in the beginning (Mk 1,14). The main problem lies in the choice between two opposing models of the messianic function of Jesus: a messianism of glory and power, and a messianism of humility, suffering and death. The healings and exorcisms worked by Jesus in the previous day (Mk 1,23-28.29-31.32-34) had revived the enthusiasm of the crowd and disciples. Behind this purely external reaction hides the satanic temptation to choose a way of earthly glory and material success. By going into the deserted place – the home of Satan – Jesus relived the first experience of the desert: there He was tested and He was victorious over evil. This victory was facilitated by the prayer that allowed Jesus to discern the will of the Father and to renew his eternal choice to fulfill this will up to the end.